The implementation of PBL integrated with STEM in the material of Temperature and Its Changes to the Improvement of Students’ Creative Thinking Skills and Learning Results - Ida Madyani; Sri Yamtinah; Suryadi Budi Utomo (Journal of Educational Science and Technology (EST), 2019)
This study aims to determine the effect of implementing PBL integrated with STEM in the materials of temperature and its changes in creative thinking skills and learning outcomes. The research method was a quasi-experimental research design with non-equivalent pretest and posttest control group. Samples were selected by purposive sampling technique. Data collection instruments were creative thinking skills and knowledge tests. The analysis technique was a different test (t-test) to determine differences in the ability to think creatively and learning outcomes aspects of knowledge, and the N-gain test to determine the effectiveness of the learning method applied. The results of this study indicate that: (1) there were differences in learning outcomes and creative thinking abilities between the control and the experimental classes (2) the effectiveness test identified that the science learning using PBL integrated with STEM is quite effective in increasing the ability to think creatively.